2011
DOI: 10.1021/ja203574u
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoglycosyltransferase Catalyzes Nonglycosidic C–N Coupling in Validamycin A Biosynthesis

Abstract: Glycosyltransferases are ubiquitous in nature. They catalyze a glycosidic bond formation between sugar donors and sugar or non-sugar acceptors to produce oligo/polysaccharides, glycoproteins, glycolipids, glycosylated natural products, and other sugar-containing entities. However, a trehalose 6-phosphate synthase-like protein has been found to catalyze an unprecedented non-glycosidic C-N bond formation in the biosynthesis of the aminocyclitol antibiotic validamycin A. This dedicated ‘pseudoglycosyltransferase’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 30 publications
0
53
0
Order By: Relevance
“…As described above, this hybrid compound is relatively unstable, requiring early termination of incubation and immediate analysis of the sample for clear observation of the product. Its low stability may explain why this product was not observed in our previous experiments (Asamizu et al, 2011). In light of the present results, we conclude that the C-terminal domain of VldE can recognize both GDPvalienol ( K m 0.06 ± 0.012 mM) (Asamizu et al, 2011) and GDP-glucose ( K m >2.2 mM) as substrate, but with >37-fold greater affinity toward GDP-valienol.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…As described above, this hybrid compound is relatively unstable, requiring early termination of incubation and immediate analysis of the sample for clear observation of the product. Its low stability may explain why this product was not observed in our previous experiments (Asamizu et al, 2011). In light of the present results, we conclude that the C-terminal domain of VldE can recognize both GDPvalienol ( K m 0.06 ± 0.012 mM) (Asamizu et al, 2011) and GDP-glucose ( K m >2.2 mM) as substrate, but with >37-fold greater affinity toward GDP-valienol.…”
Section: Resultsmentioning
confidence: 69%
“…Both GDP-valienol and validamycin 7-phosphate were prepared according to procedures reported previously (Asamizu et al, 2011). As expected, chimera-1 was able to catalyze the coupling between GDP-glucose and validamine 7-phosphate to give a hybrid pseudo-aminodisaccharide with an apparent K m value of 1.1 ± 0.07 mM and k cat / K m 0.15 s −1 •mM −1 for GDP-glucose and K m 0.975 ± 0.1 mM and k cat / K m 0.11 s −1 •mM −1 for validamine 7-phosphate (Figures 4K and S5E–F).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, is the Ncontaining carbasugars such as validamine and valienamine, which have proven to be lead compounds for the development of clinically important agents such as acarbose ( Fig. 1) 2 . It has been shown that the valienamine moiety in acarbose mimics the oxocarbenium ion-like transition state that binds to and inhibits α-glucosidase 3 .…”
Section: Introductionmentioning
confidence: 99%